Effect Of Bilingualism On An Individual’s Personality: A Psychological And Sociolinguistic Analysis - Biju, Krishnaprabha (Journal of Posthumanism, 2025)
Background: The dual-identity hypothesis suggests that bilingualism induces personality shifts depending on the language used and its associated cultural context. Despite increasing research interest, the evidence remains scattered across cognitive, sociolinguistic, and neurocognitive studies, limiting a unified understanding of these dynamics. Objective: This study investigates how bilingualism influences personality expression, testing the dual-identity hypothesis through a combination of sociolinguistic, cognitive, and neurocognitive approaches. It aims to uncover the mechanisms underpinning these shifts, including cultural frame switching, emotional regulation, and neurocognitive adaptability. Methods: Employing a mixed-methods design, the study integrates: Behavioral Assessments: Real-time ecological momentary assessments to measure personality expressions in different linguistic contexts. Neuroimaging Techniques: Functional MRI (fMRI) and EEG to explore neural correlates of cultural and linguistic switching. Longitudinal Surveys: Multi-year tracking of personality development in diverse bilingual populations, spanning balanced and unbalanced bilinguals and typologically distinct language pairs.Findings: The results provide robust evidence of personality modulation in bilinguals, showing: Increased openness and extraversion in culturally dominant languages. Reduced neuroticism in contexts aligned with secondary cultural identities. Distinct neural activation patterns during language switching, supporting the neural basis of cultural frame switching. Long-term personality stability, with greater adaptability observed in balanced bilinguals.Significance: Introducing the "Dual-Identity Personality Framework", the study bridges sociolinguistic theories and neurocognitive models to explain personality shifts in bilinguals. It has broad applications in global workforce development, multicultural education, mental health interventions, and policy-making, addressing identity and adaptability in increasingly multilingual societies.